Characteristics and Clinical Course of Patients with Acute Myocardial Infarction and ST-segment Elevation with and without Interatrial Block - Francisco de Jesús Valladares Carvajal; Verónica Mercedes Carretero Acosta; Raimundo Carmona Puerta; Aymara Marcia Hernández Cardoso; Ernesto Julio Bernal Valladares (Revista Finlay, 2023)
Foundation: it is novel to establish the relationship between interatrial block and acute myocardial infarction with ST-segment elevation due to the few studies that address the subject. Objective: to evaluate the characteristics and clinical evolution of patients with ST-segment elevation acute myocardial infarction with and without interatrial block. Methods: a descriptive and correlational study was carried out in progressive care units of the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos. 169 subjects with a diagnosis of ST-segment elevation myocardial infarction divided into two groups with and without interatrial block were selected. Demographic variables were analyzed: age, sex, skin color and between clinics: toxic habits; (smoker, ex-smoker); medical history (myocardial infarction, angina, peripheral arterial disease, arterial hypertension, type 2 diabetes mellitus, chronic kidney disease; infarct location (anterior, inferior, left bundle branch block); complications: heart failure, atrial fibrillation, ventricular tachycardia/ventricular fibrillation, atrioventricular conduction disorders, mechanical complication, post infarction angina, arterial embolism) and discharge status (alive or deceased). Results: 52.17 % of patients with ST-segment elevation myocardial infarction with interatrial block developed heart failure, vs 29.45 % among patients without block with statistical significance (p = 0.03). The relationship between the occurrence or not of complications (as well as the state at discharge) and the presence or not of blockade was highly significant (p=0.01). Conclusions: the detailed analysis, in this context, of the p wave of the electrocardiogram should be routine, since the documentation of interatrial block could be related to the clinical course of the patients.